Morphometry and abnormality evaluation of sex-sorted sperm of spotted buffalo (Tedong bonga) - KAIIN, EKAYANTI MULYAWATI; GUNAWAN, MUHAMMAD; MAULANA, TULUS (Nusantara Bioscience, 2017)
Kaiin EM, Gunawan M, Maulana T. 2017. Morphometry and abnormality evaluation of sex-sorted sperm of spotted buffalo (Tedong bonga). Nusantara Bioscience 9: 175-180. This research aimed to determine the morphometry and the abnormality of the spotted buffallo (Tedong bonga) sperm after the separation of X and Y-chromosome-bearing sperms. Semen was collected from the spotted buffalo bull by using an artificial vagina.The semen quality was evaluated macro- and microscopically. Semen that met the required standard were subjected to separation by using Bovine Serum Albumin (BSA) 5% and 10% column method. The quality of sex-sorted sperm was evaluated microscopically, including motility, concentration, viability, abnormality and intact plasma membrane. Smear preparation using Eosin-Nigrosin dyes was made for sperm morphometry and abnormality evaluation.The evaluation of sperm morphometry and abnormality was conducted on 200 sperm cells for each observation and repeated in triplicates of observation, by using Axiovision Imager Z microscope at objective and ocular magnifications 40x and 10x, respectively.The morphological parameters observed were including the length and the width of head sperm and the head area of sperm X or Y. The abnormality parameter consisted of primary and secondary abnormalities. The data were analyzed descriptively. The results showed that the head size of the Y sperm of spotted buffalo (27.16 Î¼m2) was smaller than that of the X sperm (29.86 Î¼m2) with the abnormality of the Y sperm (7.85%) was also lower than that of the X sperm (9.7%).